Thermo-Responsive Gel Containing Hydroxytyrosol-Chitosan Nanoparticles (Hyt@tgel) Counteracts the Increase of Osteoarthritis Biomarkers in Human Chondrocytes - Anna Valentino; Raffaele Conte; Ilenia De Luca; Francesca Di Cristo; Gianfranco Peluso; Michela Bosetti; Anna Calarco (MDPI AG, 2022)
Although osteoarthritis (OA) is a chronic inflammatory degenerative disease affecting millions of people worldwide, the current therapies are limited to palliative care and do not eliminate the necessity of surgical intervention in the most severe cases. Several dietary and nutraceutical factors, such as hydroxytyrosol (Hyt), have demonstrated beneficial effects in the prevention or treatment of OA both in vitro and in animal models. However, the therapeutic application of Hyt is limited due to its poor bioavailability following oral administration. In the present study, a localized drug delivery platform containing a combination of Hyt-loading chitosan nanoparticles (Hyt-NPs) and in situ forming hydrogel have been developed to obtain the benefits of both hydrogels and nanoparticles. This thermosensitive formulation, based on Pluronic F-127 (F-127), hyaluronic acid (HA) and Hyt-NPs (called Hyt@tgel) presents the unique ability to be injected in a minimally invasive way into a target region as a freely flowing solution at room temperature forming a gel at body temperature. The Hyt@tgel system showed reduced oxidative and inflammatory effects in the chondrocyte cellular model as well as a reduction in senescent cells after induction with H2O2. In addition, Hyt@tgel influenced chondrocytes gene expression under pathological state maintaining their metabolic activity and limiting the expression of critical OA-related genes in human chondrocytes treated with stressors promoting OA-like features. Hence, it can be concluded that the formulated hydrogel injection could be proposed for the efficient and sustained Hyt delivery for OA treatment. The next step would be the extraction of "added-value" bioactive polyphenols from by-products of the olive industry, in order to develop a green delivery system able not only to enhance the human wellbeing but also to promote a sustainable environment.